Long‐term declines in stream and river inorganic nitrogen (N) export correspond to forest change. Issue 2 (24th May 2016) - Lucas, Richard W.; Sponseller, Ryan A.; Gundale, Michael J.; Stendahl, Johan; Fridman, Jonas; Högberg, Peter; Laudon, Hjalmar
Abstract: Human activities have exerted a powerful influence on the biogeochemical cycles of nitrogen (N) and carbon (C) and drive changes that can be a challenge to predict given the influence of multiple environmental stressors. This study focused on understanding how land management and climate change have together influenced terrestrial N storage and watershed inorganic N export across boreal and sub‐arctic landscapes in northern Sweden. Using long‐term discharge and nutrient concentration data that have been collected continuously for over three decades, we calculated the hydrologic inorganic N export from nine watersheds in this region. We found a consistent decline in inorganic N export from 1985 to 2011 over the entire region from both small and large watersheds, despite the absence of any long‐term trend in river discharge during this period. The steepest declines in inorganic N export were observed during the growing season, consistent with the hypothesis that observed changes are biologically mediated and are not the result of changes in long‐term hydrology. Concurrent with the decrease in inorganic N export, we report sustained increases in terrestrial N accumulation in forest biomass and soils across northern Sweden. Given the close communication of nutrient and energy stores between plants, soils, and waters, our results indicate a regional tightening of the N cycle in an already N‐limited environment as a result of changes in forest management and climate‐mediated growth increases. Our results are consistent with declining inorganic N efflux previously reported from small headwater streams in other ecosystems and shed new light on the mechanisms controlling these patterns by identifying corresponding shifts in the terrestrial N balance, which have been altered by a combination of management activities and climate change.